Radial Profiles of local solids distribution in a high-loaded Riser-Reactor measured with x-ray computed Tomography - Wirth, Karl-Ernst; et al. (Proceedings of the ASME Heat Transfer Division, 1998)
Since years high-loaded riser-reactors have been used successfully for different commercial applications, e.g. for fluid catalytic cracking. The fundamental study of hydrodynamics of such reactors will help to improve the design and operating conditions of existing plants and may lead to higher conversion rates and selectivity. The solids concentration distribution of a riser with an inner diameter of 0.19 m and 15 m height is investigated with x-ray computed tomography with a minimum spatial resolution of 0.2 mm and 0.4 mm thickness. A number of experiments have been carried out with narrowly size distributed glass beads between 50 and 70 μm at superficial gas velocities from 2 to 7 m/s. Even at higher circulation rates obtained radial solids concentration profiles still show a typical core-annulus structure, which gets more uniform at higher elevations.
UnivIS-Import:2015-04-16:Pub.1998.tech.ITC.mechve.radial_19
Keywords: riser; fluidized; bed